VIDEO TO AMPLIFY BANKING STUDENT’S WRITING PERFORMANCE - Fenny Thresia (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2014)
Abstract: Writing is activity to mix between the idea, vocabulary and also grammar. By looking at the problems, the teacher should make the proper method in teaching writing in order to increase the students writing skill and also make the writing be an interesting activity to them. One of the good methods is using video as a media of learning. Video can stimulates the student’s to makes them easier to find the ideas in writing process, because video included 3D and also the complex media. This research was aimed at detecting the influence of using video as a media toward student's writing performance.This research was quantitative research form and the sampling technique was random sampling. The data collection method in this research used the documentation and test that consist of pre-test and pos-test. The data analysis technique of this research used T-test as the hypothetical statistic calculation. Based on the research analysis, there is any positive and significant influence of using video as a media toward students’ writing performance of banking students.